Antagonistic effect of humic acid and naphthalene on biochar colloid transport in saturated porous media. (December 2017) - Yang, Wen; Wang, Yang; Shang, Jianying; Liu, Kesi; Sharma, Prabhakar; Liu, Juan; Li, Baoguo
Abstract: Biochar is a carbon-enriched material derived from organic material pyrolysis under no/limited oxygen, which is widely used for soil amendment, carbon sequestration, and contaminated soil remediation. This study aims to explore the interplay effect of humic acid (HA) and naphthalene on transport of biochar colloid (BC) in saturated porous media. A series of column experiments were conducted to study BC mobility at different concentrations of HA (0, 10, and 20 mg L −1 ) and naphthalene (0, 0.1, and 0.2 mg L −1 ). The results showed that increasing HA concentration promoted BCs mobility in porous media by increasing the electrostatic and steric interaction between BCs and collectors. However, the presence of naphthalene reduced the mobility of BCs with naphthalene increasing from 0 to 0.2 mg L −1, because the nonpolar naphthalene adsorbed onto the biochar surface and shielded the negative charge of BCs. The maximum breakthrough C/C0 of BCs was increased from 0.7 to 0.8 with increasing HA concentration from 0 to 20 mg L −1 in the presence of 0.1 mg L −1 naphthalene. This meant that HA still played the role to increase the electrostatic repulsion between BCs with HA and collectors when naphthalene was adsorbed on BCs. BCs breakthrough curves were well described by the two-site kinetic retention model including one reversible retention site and another irreversible retention site. The antagonistic effects of naphthalene and HA on BC transport suggested that the mobility of colloidal biochar particles in naphthalene-polluted soil was dependent on the coupled effects of naphthalene and natural organic matter. Graphical abstract: Highlights: Humic acid increased biochar colloid transport in saturated porous media. Naphthalene decreased the mobility of biochar colloid in porous media. Naphthalene and humic acid showed the antagonistic effect on biochar colloid transport. Biochar colloid breakthrough curves were well described by the two-site kinetic retention model.